2023
DOI: 10.1371/journal.pone.0281187
|View full text |Cite
|
Sign up to set email alerts
|

Clonal isolates of Treponema pallidum subsp. pallidum Nichols provide evidence for the occurrence of microevolution during experimental rabbit infection and in vitro culture

Abstract: The recent development of a system for long-term in vitro culture of the syphilis spirochete, Treponema pallidum subsp. pallidum, has introduced the possibility of detailed genetic analysis of this bacterium. In this study, the in vitro culture system was used to isolate and characterize clonal populations of T. pallidum subsp. pallidum Nichols, the most widely studied strain. In limiting dilutions experiments, it was possible to establish cultures with inocula as low as 0.5 T. pallidum per well despite the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…pallidum Nichols strain revealed that in vivo-grown and in vitro-cultured T. pallidum genome sequences are highly similar and any observed sequence differences are unlikely to account for the 11 novel genome errors identified in the present in vitro study. Another limitation is that the Nichols strain used in our previous and present study was originally isolated in 1912 from the cerebrospinal fluid (CSF) of a secondary syphilis patient .…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…pallidum Nichols strain revealed that in vivo-grown and in vitro-cultured T. pallidum genome sequences are highly similar and any observed sequence differences are unlikely to account for the 11 novel genome errors identified in the present in vitro study. Another limitation is that the Nichols strain used in our previous and present study was originally isolated in 1912 from the cerebrospinal fluid (CSF) of a secondary syphilis patient .…”
Section: Resultsmentioning
confidence: 62%
“…A limitation of these findings is the possibility that the remaining nine potential proteome errors identified in this study but not detected from in vivo-grown treponemes 25 are due to potential “artificial” conditions introduced during in vitro treponeme culture and/or possible post-translational modifications such as N-terminal proteolytic processing. However, genome sequencing of an in vitro-cultured T. pallidum Nichols strain revealed that in vivo-grown and in vitro-cultured T. pallidum genome sequences are highly similar 78 and any observed sequence differences are unlikely to account for the 11 novel genome errors identified in the present in vitro study. Another limitation is that the Nichols strain used in our previous 25 and present study was originally isolated in 1912 from the cerebrospinal fluid (CSF) of a secondary syphilis patient.…”
Section: Resultsmentioning
confidence: 68%
“…Genetic adaptation of TPA strains to rabbit infection during long-term propagations in rabbits is widely speculated, but there is no clear genetic evidence of this process. While Giacani et al [20] suggested the presence of such mutations by genetic comparisons of the Nichols strain to other Nicholslike strains and Edmondson et al [21] demonstrated the microevolution of the Nichols strain, Grillova ´et al [22] tested the DAL-1 strain for genome stability and adaptation in continual rabbit cultivation representing more than 100 TPA generations (i.e., 142 days) during which the allelic profile of DAL-1 remained stable. Moreover, the genetic adaptation to rabbits appears to be a relatively long process corresponding to the relatively low estimated mutation rates of pathogenic T. pallidum, where it took over a decade to fix a single mutation [23,24].…”
Section: Plos Onementioning
confidence: 99%
“…Assemblies were then produced using MiniMap2 14 and the NYMC01 genomic sequence as template, followed by iterative refinements using refined templates to resolve discrepancies. 15 Sequence ambiguities with <80% nucleotide agreement at a given position were designated as N. The numbers of N's in the NYCM01, P-22-20198_RA, and R-22-10139_RA assemblies were 120, 180, and 213, respectively, with most of these being in the highly variable tprK gene.…”
Section: Genome Assembly and Data Analysismentioning
confidence: 99%